(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2016)
Intractable fecal and urinary incontinence, often associated with myelomeningocele (MMC), usually prevents children from achieving physical and social independence. The Malone Antegrade Continence Enema (MACE) procedure, often performed in conjunction with a Mitrofanoff procedure to gain fecal & urinary continence, can help these patients to attain a better quality of life. In patients, who underwent the combined Mitrofanoff and MACE procedures simultaneously, the success rate is- 83% satisfactory for both bowel & urinary continence. With this procedure we report here, for the first time in Bangladesh, to the best of our knowledge, an association between two previously described techniques (the Mitrofanoff principle and MACE), that can solve the problem of dual incontinence in children with MMC. The case involved a 14 years old boy with total neurogenic feco-urinary incontinence following excision & repair of MMC at the age of 4 months. After the surgery, the boy is continent with normal renalfunction. J. Paediatr. Surg. Bangladesh 6(1): 28-31, 2015 (Jan)